IDENTIFICATION OF LAYERS PRESENT IN A CONTEMPORARY CERAMIC USING LASER-INDUCED PLASMA SPECTROSCOPY - Luízar Obregón, Celina (2021)
In this work, laser-induced plasma spectroscopy was used to identify the elemental composition, at different depths, of a commercial Peruvian ceramic. The IVEA MobiLIBS system and IUMTEK TX1000 system were used, under environmental conditions and 5.6 mJ of energy, forming craters of approximately 60 μm in diameter. To improve accuracy, repetitions of the impact points were performed, accumulating the signals at the same depth. The blue and white pigments that covered it, as well as the matrix paste, were characterized, making different levels of penetration in the material, obtaining their respective elemental composition. This allowed finding the difference between stratigraphic layers, based mainly on the variation of the intensities of Copper, Titanium, Carbon and other characteristic elements of the clays that make up the matrix paste. Contemporary pottery was found to have sequential layers of decoration, engobe and matrix paste.